KUALITAS PELAYANAN PUBLIK KANTOR KECAMATAN MEKARSARI KABUPATEN BARITO KUALA BERDASARKAN INDEKS KEPUASAN MASYARAKAT (IKM) - Bakhtiar Bakhtiar; Rizalul Gadi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
The results of the study showed that the results of the community satisfaction survey on public service types of population administration in Mekarsari District Barito Kuala Regency based on the Community Satisfaction Index Value (IKM) was 77.25 which was included in the "Good" category, where the highest satisfaction value was for the service procedure element , and Cost / Tariff (3.6) and the lowest satisfaction value is for the Handling of Complaints, Suggestions and Inputs with a value (2.1). Efforts to improve service performance: (a). make proposals to add employees to the district government, (b). maximizing available resources, (c). Open opportunities for school children and students who want to carry out an internship program, (d). For the quality of human resources, provide opportunities to improve their competence, both advanced studies and attending education and training, (e). While other efforts related to facilities and infrastructure such as computer equipment, the sub-district has also proposed additional procurement of computer equipment to the district government.